2014
DOI: 10.1016/j.jns.2014.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microbleeds in a multiethnic elderly community: Demographic and clinical correlates

Abstract: Background Microbleeds, small perivascular collections of hemosiderin manifested radiologically as hypointensities on gradient-echo magnetic resonance imaging (MRI), are important markers of small vessel pathology. Despite their clinical relevance, little is known about their prevalence and demographic correlates, particularly among ethnically diverse older adults. We examined demographic and clinical correlates of regional microbleeds in a multi-ethnic cohort and examined categorization schemes of microbleed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 52 publications
5
49
1
Order By: Relevance
“…Individuals with 2 or more lobar microbleeds had an accelerated rate of speed/executive function decline over the 9-year period preceding the MRI scan relative to individuals with fewer than 2 microbleeds. Unsurprisingly and as we have reported previously (Wiegman, et al, 2014), individuals with more than 2 microbleeds also had increased evidence of ischemic cerebrovascular disease (i.e., WMH and infarct).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Individuals with 2 or more lobar microbleeds had an accelerated rate of speed/executive function decline over the 9-year period preceding the MRI scan relative to individuals with fewer than 2 microbleeds. Unsurprisingly and as we have reported previously (Wiegman, et al, 2014), individuals with more than 2 microbleeds also had increased evidence of ischemic cerebrovascular disease (i.e., WMH and infarct).…”
Section: Discussionsupporting
confidence: 82%
“…Beginning in 2009, participants with initial MRI scans were invited for a follow-up MRI scan, leading to a total of 339 subjects with repeat MRI; 243 of the 339 had T2*-weighted gradient echo (GRE) scans for microbleed assessment (Wiegman et al, 2014). For the current analysis, we examined cognition data starting in 1999 and excluded subjects meeting clinical criteria for dementia at the time of the GRE MRI scan (N=46), resulting in a sample of 197 subjects (mean age: 84.15+/− 5.02 years) that comprised the study group reported here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18, 19 In the ARIC study, no significant difference in risk of CMB presence or location were detected by race. Two prior racially and ethnically diverse studies on CMBs revealed no difference in CMB frequency between black, white and Hispanic individuals 20, 21 . Despite the association of CMBs with imaging markers of small-vessel disease, diabetes was not associated with CMBs in the present study or in the Framingham or Rotterdam studies.…”
Section: Discussionmentioning
confidence: 75%
“…81,84 Prevalence was similar in a multiethnic cohort, the Washington Heights-Inwood Columbia Aging Project. 86 Technical and measurement-related factors may influence CMB prevalence rates. Most important, MRI parameters such as longer echo time, smaller interslice gap, and the use of 3-dimensional acquisition, a higher magnetic field, and newer sequences such as susceptibility-weighted imaging can increase the ability to detect microbleeds by 2-to 3-fold.…”
Section: Cerebral Microbleedsmentioning
confidence: 99%